Appropriate fiscal policy over the business cycle: Proper stimulus policies can work - Philip E. Graves (Center for Economic Studies and ifo Institute (CESifo), 2010)
Fiscal policy has become quite controversial in the post-Keynesian era, the debate over the Obama stimulus package being a contentious recent example. Some pundits go so far as to take the position that macroeconomic theory has failed to meaningfully progress in terms of providing useful recommendations for policy-makers, particularly in times of recession. Others take the laissez-faire view that policy reactions to the business cycle do not help in a rational expectations world and indeed do harm by increasing uncertainty. Still others, while not necessarily viewing themselves as in any sense 'Keynesian,' have a nagging feeling that sometimes doing nothing must be worse than doing something...but what to do? Sensible guidance is provided here on how governments should spend taxpayer dollars and on how that spending should change under varying economic conditions. The nature of public goods, namely whether they are complements, substitutes, or neutral to private goods, is seen to be critical to such decisions.
Keywords: E12; E13; E32; E61; E62; E66; H11; H30; H50; 330; fiscal policy; business cycles; public goods; recessions; boomtimes; Antizyklische Finanzpolitik; Finanzpolitik; Konjunktur; Öffentliches Gut; USA